Double-stranded phosphodiester cytosine-guanine oligodeoxynucleotide complexed with calcium phosphate as a potent vaccine adjuvant for activating cellular and Th1-type humoral immunities - Hanagata N (Dove Medical Press, 2017)
Nobutaka Hanagata,1,2 Xianglan Li,1 Min-Hua Chen,1 Jie Li,1 Shinya Hattori1 1Nanotechnology Innovation Station, National Institute for Materials Science, Tsukuba, 2Graduate School of Life Science, Hokkaido University, Sapporo, Japan Abstract: Conventional class B cytosine-guanine (CpG) (CpG-B) oligodeoxynucleotide (ODNs) consisting of a single-stranded (ss) phosphorothioate (PT) backbone (ss CpG-B-PT) is converted from a proinflammatory cytokine inducer to a type-I interferon (IFN) inducer when complexed with cationic materials. In this study, we designed ss CpG-B and double-stranded (ds) CpG-B ODNs with a phosphodiester (PD) backbone (ss CpG-B-PD and ds CpG-B-PD, respectively) that became type-I IFN inducers upon complexation with Lipofectamine 2000 (Lipo), a cationic liposome. The ds CpG-B-PD complex induced higher IFN-β expression in mouse macrophage-like RAW264 cells than ss CpG-B-PD and ss CpG-B-PT complexes. The fold induction of IFN-β increased with the number of CpG motifs in ds CpG-B-PD, and a complex of ds CpG-B-PD consisting of 72 base pairs with nine CpG motifs (ds CpG-B72-PD) and Lipo showed the highest capacity to induce IFN-β. The materials and method used for complexation influenced the degree of IFN-β induction: ds CpG-B72-PD entrapped by calcium phosphate (CaP) (ds CpG-B72-PD/CaP) showed a higher induction capacity than ds CpG-B72-PD adsorbed onto the CaP surface. Entrapment of ds CpG-B72-PD by CaP also enhanced the induction of the proinflammatory cytokine interleukin-12. Vaccinating mice with ds CpG-B72-PD/CaP in conjunction with ovalbumin (OVA) increased the ratios of OVA-specific CD8+ T cells to total CD8+ T cells in peripheral blood and of OVA-specific IgG2a associated with helper T (Th)1 cells to OVA-specific IgG1 associated with Th2 cells. These results indicate that ds CpG-B72-PD/CaP is an effective vaccine adjuvant that can activate both cellular and Th1-type humoral immune responses. Keywords: CpG oligodeoxynucleotide, calcium phosphate, vaccine adjuvant, cellular immunity, humoral immunity